The Role Of The State Towards Data Protection In The Use Of Artificial In-telligence Through The Cooperation Between Countries In Asean - Gandawidjaja, Yanly; Bunawan, Petra; F. X. Purba, Christian Josua (IHSA Institute, 2025)
Cutting-edge technology, including Artificial Intelligence (AI), is essential for supporting human activities, automating tasks, and processing vast amounts of data. However, the use of AI raises concerns about data security, privacy, and the role of humans in legal decision-making. This study explores Indonesia's role in protecting personal data amidst AI advancements and its efforts to establish cross-border data protection cooperation within ASEAN. Using a normative juridical research method, this study examines legal aspects, literature, and case studies through conceptual, analytical, and case approaches, analyzing the data qualitatively. Indonesia ensures legal certainty in personal data protection through Law No. 27 of 2022 on Personal Data Protection. Additionally, Minister of Communication and Information Circular Letter No. 9 of 2023 on AI Ethics serves as a guideline for electronic system administrators to implement technology responsibly. At the regional level, Indonesia collaborates with ASEAN countries to address cross-border data protection. It participated in the formulation of the